A new genus and two new species of Thyasiridae associated with methane seeps off Svalbard, Arctic Ocean. Issue 4 (21st April 2017) - Åström, Emmelie K.L.; Oliver, P. Graham; Carroll, Michael L.
ABSTRACT: Bivalves have been found in unique benthic assemblages associated with active methane seeps and mounds along the western and southern margins of the Svalbard shelf (75–79°N) at 350–380 m depth. Among the samples collected were a number of shells of Thyasiridae that are distinct from any species previously described. Here we describe one new genus Rhacothyas gen. nov. and two new species Thyasira capitanea sp. nov . and Rhacothyas kolgae sp. nov ., including their distinguishing characteristics and the environmental setting where they were found. Thyasira capitanea sp. nov. is large compared with many other thyasirids, has an equilateral shell and demarcated zones on the median and anterior areas along with a distinct posterior sulcus. Rhacothyas kolgae sp. nov . is unique among other thyasirid genera and species regarding its characteristic outline, sunken lunule, lack of submarginal sulcus and wrinkled surface. Furthermore, we discuss their present occurrence in the context of the glaciomarine history of the Svalbard margin. We posit that these new species, after the deglaciation of the Barents Sea Ice Sheet, may have originated from other chemosynthetic or reducing environments along the Atlantic shelf margin or the southern Barents Sea shelf by following the net transport of the North Atlantic Current rather than having evolved in situ . http://zoobank.org/urn:lsid:zoobank.org:pub:0F3DCFD6-05C9-4E76-803E-655ACD3AF335